STUDI KASUS: MANUVER MC ROBERT PADA PERTOLONGAN PERSALINAN DENGAN DISTOSIA BAHU - Arvicha Fauziah; Kasmiati Kasmiati (Jurnal Kebidanan, 2023)
Shoulder dystocia is an obstetric emergency because of the limited time of delivery where the normal value of the time interval for delivery of the head and delivery of the whole body is 24 seconds, but in the case of shoulder dystocia, it lasts 79 seconds resulting in fetal trauma and complications for the mother. Its occurrence is difficult to predict after the head is born, the head is like a turtle and the shoulder delivery is difficult. Mc Robert's Manuver is most effective for front shoulder delivery assistance. One of the factors causing shoulder dystocia is multiparity and maternal power during childbirth. This case study describes the management of midwifery care for Mrs. R, a 31 year old multiparous woman, who experienced shoulder dystocia during labour. Handling efforts carried out by the Mc Robert Manuver method. Case studies use assistive devices in the form of a midwifery care format for mothers giving birth and status sheets or patient documentation and a list of interview questions. Data analysis used is data collection, data interpretation, identification of diagnoses, immediate needs and collaboration, planning, implementation, evaluation and drawing conclusions. The result of the case study is the delivery process with basic assistance in shoulder dystocia using the Mc Robert Manuver method. Health workers must be able to master the skills of emergency delivery assistance in efforts to treat shoulder dystocia.